The abortion campaign: a study of moral reform and status protest - Clarke, Alan Henry (1984)
This study focuses on three major pressure groups involved in the abortion campaign, namely, the two anti-abortion organisations 'Life' and the Society for the Protection of the Unborn Child, and the National Abortion Campaign, a grassroots organisation which supports the campaign for 'A Woman's Right to Choose'.